3‐D laser images of splash‐form tektites and their use in aerodynamic numerical simulations of tektite formation. (29th April 2014) - Samson, C.; Butler, S.; Fry, C.; McCausland, P. J. A.; Herd, R. K.; Sharomi, O.; Spiteri, R. J.; Ralchenko, M.
Abstract Ten splash‐form tektites from the Australasian strewn field, with masses ranging from 21.20 to 175.00 g and exhibiting a variety of shapes (teardrop, ellipsoid, dumbbell, disk), have been imaged using a high‐resolution laser digitizer. Despite challenges due to the samples' rounded shapes and pitted surfaces, the images were combined to create 3‐D tektite models, which captured surface features with a high fidelity (≈30 voxel mm−2) and from which volume could be measured noninvasively. The laser‐derived density for the tektites averaged 2.41 ± 0.11 g cm−3. Corresponding densities obtained via the Archimedean bead method averaged 2.36 ± 0.05 g cm−3. In addition to their curational value, the 3‐D models can be used to calculate the tektites' moments of inertia and rotation periods while in flight, as a probe of their formation environment. Typical tektite rotation periods are estimated to be on the order of 1 s. Numerical simulations of air flow around the models at Reynolds numbers ranging from 1 to 106 suggest that the relative velocity of the tektites with respect to the air must have been <10 m s−1 during viscous deformation. This low relative velocity is consistent with tektite material being carried along by expanding gases in the early time following the impact.